Making Sense of Jiese: An Interview Study of Members from a Porn-Free Self-Help Forum in China. - Zou, Wenxue; Zhang, Xinyu; He, Jingqi (Archives of Sexual Behavior, 2023)
About 6 million men in China engage in jiese (abstaining from masturbation and porn) and call themselves jieyou (porn-free self-help community members). In this article, we sought to unpack how the idea of jiese took root in Chinese historical, social, and cultural contexts by interviewing 32 jieyou. Guided by the sensemaking theory, we conducted a critical discourse analysis of participants' responses and ended up identifying four major themes: embodied experiences, jiese as rational and noble, reconstructing the subjectivity of jieyou, and nationalistic sentiments. We found out that jieyou tended to justify their abstinence by seeking sources of legitimacy in traditional Chinese culture, the ideology of healthism, science, and patriotic discourses. We argue that jiese reflects young men's contradictory cultural practices of conservatism, self-medicalization, and neoliberal governmentality.